Self-Electrified Water is a Powerful Toolbox for the Production of Chemicals and Energy - Galembeck, Fernando; Santos, Leandra P.; Burgo, Thiago A.L. [UNESP]; Galembeck, Andre (Sociedade Brasileira de Quimica (SBQ), 2024)
Three groups of unexpected experimental findings were published in the past twenty years in different research areas, opposing current paradigms, and supporting the following statements: (i) water is becoming the ideal medium for chemical synthesis; (ii) water is an electrifying agent of most materials; (iii) macroscopic matter is formed by charge mosaics that are often the outcomes of surface processes at the aqueous interfaces. These statements provoke major changes in chemical thinking that have a common feature: the behavior of chemicals in aqueous electrified interfaces may largely differ from their behavior in bulk and theoretical predictions. This review discusses eight widely accepted statements familiar to chemists, students, professors, and teachers, but challenged by many experimental findings obtained in systems having aqueous interfaces. A broader statement that is being used in this context is that the thermodynamic properties of ionic species change depending on the local electric potential, modifying their reactivity, mass transfer, and other properties. Beyond synthetic applications, atmospheric moisture is becoming a promising source of electricity. These new views create huge opportunities for chemical research and development, based on the most abundant and environmentally compatible chemical. Aqueous interfaces are thus a powerful toolbox for building a sustainable economy.
Keywords: contact charging; interfaces; Maxwell-Wagner-Sillars effect; self-electrification; “on-water” reactions